A Pan-Cancer Analysis of the Oncogenic Role of Twinfilin Actin Binding Protein 1 in Human Tumors - Huo, Gengwei; Wang, Yali; Chen, Jinliang; Song, Ying; Zhang, Cuicui; Guo, Hua; Zuo, Ran; Zhu, Fuyi; Cui, Jinfang; Chen, Weidong; Chen, Wenming; Chen, Peng (Frontiers in Oncology, 2021)
Background: Understanding common and unique mechanisms driving oncogenic processes in human tumors is indispensable to develop efficient therapies. Recent studies have proposed Twinfilin Actin Binding Protein 1 (TWF1) as a putative driver gene in lung cancer, pancreatic cancer and breast cancer, however a systematic pan-cancer analysis has not been carried out. Methods: Here, we set out to explore the role of TWF1 in 33 tumor types using TCGA (The Cancer Genome Atlas), GEO (Gene Expression Omnibus) dataset, Human Protein Atlas (HPA), and several bioinformatic tools. Results: As part of our analysis, we have assessed TWF1 expression across tumors. We found that over-expression of TWF1 generally predicted poor OS for patients with tumors with high TWF1 expression, such as mesothelioma, lung adenocarcinoma, cervical cancer and pancreatic adenocarcinoma. We also assessed the mutation burden of TWF1 in cancer and the TWF1-associated survival of cancer patients, compared the phosphorylation of TWF1 between normal and primary tumor tissues and explored putative functional mechanisms in TWF1-mediated oncogenesis. Conclusions: Our pan-cancer analysis provides a comprehensive overview of the oncogenic roles of TWF1 in multiple human cancers.